If Your Language Was a Car… The Object(s) of Linguistic Research, or: Towards a Shared Geography of Linguistics - Harder, Peter (HERMES - Journal of Language and Communication in Business, 2011)
The article suggests that there are underexplored possibilities for fruitful communication between formal and functionalist linguistics. A key issue is the question of exactly what each approach is aiming to capture about language. This is especially relevant for understanding the status of claims about autonomy. The role of distributional regularities and their precise relations with semantic motivation is argued to be a shared problem that could fruitfully be addressed from both sides of the divide – and the role of niche construction as a dimension of evolutionary theory is put forward as providing a new take on the innateness debate. Torben Thrane’s work is discussed as an illustration example.